Спеціальний міжнародний трибунал із розслідування злочину агресії росії проти України: правовий аналіз, міжнародна юрисдикція та виклики - Войціховський, А. В.; Voitsikhovskyi, A. V.; Бакумов, О. С.; Bakumov, O. S.; Андрій Войціховський (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 3 (102), ч. 1. - С. 203-217, 2023)
Досліджено проблемні питання утворення спеціального міжнародного трибуналу із розслідування злочину агресії росії проти України. Розкрито організаційно-правові зусилля Ради Європи, НАТО, ОБСЄ та ЄС у формуванні міжнародного механізму з притягнення до відповідальності вищого політичного і військового керівництва рф за агресію проти України. Акцентовано увагу на міжнародно-правовому аналізі моделей майбутнього спеціального трибуналу, розкрито його юрисдикцію. Визначено основні виклики для міжнародного співтовариства щодо створення спеціального міжнародного трибуналу з розслідування злочину агресії росії проти України.

The article is one of the first attempts to provide a comprehensive study of the theoretical and practical foundations for the scientific idea of establishing a Special International Tribunal on investigation of the russian aggression against Ukraine and determining its place in the system of international criminal justice. The problematic issues of establishing a Special International Tribunal to investigate the russian aggression against Ukraine have been studied. The organisational and legal efforts of the Council of Europe, NATO, OSCE and the EU in creating an international mechanism to bring the top political and military leadership of russia to justice for its aggression against Ukraine have been revealed. The attention is focused on the international legal analysis of the models for the future special tribunal, as well as its jurisdiction. The main challenges for the international community in establishing a special international tribunal to investigate the russian aggression against Ukraine are identified. It has been noted that the establishment of a Special International Tribunal to investigate the crime of russian aggression against Ukraine should become an effective mechanism for investigating and documenting violations of International Human Rights Law and International Humanitarian Law committed by russia on the territory of Ukraine with the identification of those responsible; compensation for victims and restoration of justice for the Ukrainian people from russia's full-scale armed attack; deterrence of aggressive and destabilising actions of the russian federation, which violates the sovereignty and territorial integrity of Ukraine. At the same time, the establishment of a Special Tribunal will have an impact on preventing the recurrence of such crimes, impunity and setting a precedent for similar situations in the future; it will also play an important role in strengthening international law and norms, especially in the context of armed conflicts and aggression between states; as well as it will contribute to the restoration of confidence and stability in the region and around the world, and demonstrate the solidarity of the international community with Ukraine in its struggle to restore its sovereignty and territorial integrity.

Исследованы проблемные вопросы создания специального международного трибунала по расследованию преступления агрессии России против Украины. Раскрыты организационно-правовые усилия Совета Европы, НАТО, ОБСЕ и ЕС в формировании международного механизма привлечение к ответственности высшего политического и военного руководства РФ за агрессию против Украины. Акцентировано внимание на международно-правовом анализе моделей будущего специального трибунала, раскрыта его юрисдикция. Определены основные вызовы для международного сообщества по созданию специального международного трибунала по расследованию преступления агрессии России против Украины.
Special International Tribunal on the investigation of the russian aggression against Ukraine: legal analysis, international jurisdiction and challenges
Keywords: спеціальний міжнародний трибунал; special international tribunal; специальный международный трибунал; юрисдикція; jurisdiction; юрисдикция; військова агресія; military aggression; военная агрессия; Рада Європи; Council of Europe; Совет Европы; НАТО; NATO; ОБСЄ; OSCE; ЄС; ЕС; моделі спецтрибуналу; models of special tribunals; модели спецтрибунала